Predictions of the Flow in the Intake Port of an Engine Using LES and PANS - Eidevåg, Tobias; Lindström, Martin (My University, 2013)
The airflow in the cylinder of a car engine is simulated using three different techniques. Large Eddy Simulations (LES), Partially Averaged Navier-Stokes (PANS) and Reynolds Averaged Navier-Stokes (RANS). The simulations are compared with experimental data from BMW and a benchmark designed by BMW, executed by AVL List GmbH among others. A comparison and evaluation between the three different turbulence models is made, especially differences in flow physics. The study focuses on evaluting PANS for this complex geometry as well as understanding the tumble creation in the cylinder. The computational mesh was created using ANSYS ICEM CFD and the simulations were performed with AVL FIRE.
Keywords: Strömningsmekanik; Hållbar utveckling; Transport; Fluid mechanics; Sustainable Development; Transport